PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (KANTOR DINAS SOSIAL KOTA BIMA) - Feni Haryati Susilaningsih; Abdul Kodir Djaelani; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
AbstrakThis study aims to determine the influence of organizational culture, work environment, and leadership style on employee performance. The analytical method used in this study is using the SPSS program which consists of several classical assumptions, normality, multiple linear analysis and hypothesis testing. The results of this study indicate that organizational culture variables do not affect employee performance, work environment variables affect employee performance, and leadership style variables affect employee performance. Organizational culture variables, work environment, and leadership style simultaneously or simultaneously influence employee performance Kantor Dinas Sosial Kota Bima.  Keywords: Employee Performance, Organizational Culture, Work Environment, and Leadership Style.